TI_GERICHTE 80.2023.205 vom 21. August 2023 , Procedura: ricorso, requisiti di forma, richiesta di proroga del termine, irricevibile - TI Tribunale d'appello (2023)
Procedura: ricorso, requisiti di forma, richiesta di proroga del termine, irricevibile